Effect of dietary supplementation of Baker`s Yeast (Saccharomyces cerevisiae) on the performance of broilers - Renjith P M (Department of Poultry Science, College of Veterinary and Animal Sciences, 2004)
An experiment was designed and conducted at the Department of Poultry Science to investigate the effect of feeding baker's yeast on growth, feed consumption and nutrient utilization of broilers. One hundred and forty four day old commercial broiler chicks were reared under three different treatments with four replicates per treatment. The treatment consisted of control diet with standard broiler ration (Tl ) and 1'2 and T3 with 0.3 and 0.6 per cent baker's yeast supplemented respectively with control diet. Chicks were reared under standard managemental conditions up to 8 weeks of age. Broiler starter ration was fed up to 6 weeks of age and finisher ration up to 8 weeks of age. Results of the study revealed that cumulative body weight and body weight gain up to six weeks and eight weeks of age were not affected by the inclusion of yeast. Mean weekly feed consumption recorded significant (P<0.05) difference between treatment during fifth, seventh and eighth weeks of age. Cumulative feed intake up to six weeks and eight weeks of age did not dfffer significantly. But yeast supplemented groups recorded numerically lower feed consumption compared to control group. Feed conversion ratio revealed significant difference (P< 0.05) at sixth week of age recording lower feed efficiency, in 1'2 and T3 compared to control (TJ). But cumulative feed conversion ratio from zero to six weeks and zero to eight weeks of age did not differ significantly. Supplementation of baker's yeast had no effect on processing yields and losses. Numerically lower fat deposition was recorded in yeast supplemented groups than in control group, eventhough there was no significant difference. The addition of yeast at 0.3 per cent and 0.6 per cent levels significantly increased (P<0.05) crude fiber digestibility. Other parameters like retention of dry matter, nitrogen, calcium and phosphorus were not affected by yeast supplementation. Serum protein, serum cholesterol and livability were not affected by yeast supplementation. The net profit per bird was less in yeast supplemented group compared to control group. The higher cost of feed resulted in lower economical return from the treatment groups. The result suggests that inclusion of yeast is not beneficial on economical point of view. However the lower fat deposition consequent to yeast supplementation seems to be advantageous.